Maritime Pilots’ Risky Operational Behavior Analysis Based on Structural Equation Model - Tingliu Xu; Yingjie Xiao; Zhuohong Jiang (Discrete Dynamics in Nature and Society)
In this paper, a maritime pilots’ risky behaviour related factors questionnaire is designed to identify and quantify the factors of maritime pilots’ risky operational behaviour. And a questionnaire survey was conducted, which included four scales: risk-taking behavior, risk attitude, operational reliability, and risk perception. On this basis, the Structural Equation Model (SEM) of maritime pilots’ risky operational behavior is constructed to explore the internal relationship of the variable factors affecting maritime pilots’ operational behavior. The biggest influence on maritime pilots’ safety behavior is crowd psychology, which indicates that the maritime pilot’s mental health course, the psychological guidance course system, the psychological health consultation management, and safety training should be carried out regularly. Random evaluation and attention are significantly correlated with the risky cognition of maritime pilots. The results also explore that the maritime pilots’ risky behavior related factors questionnaire has a good structure, internal consistency, and validity in Chinese maritime pilots, and it is expected to be used for the Chinese maritime pilots’ subjective risky behavior self-evaluation. In addition, with empirical evidence for pilotage safety intervention in China, this measurement can also provide scheduling and management decision support for Chinese maritime pilot stations.